Análise do sistema de medição e de fatores do ângulo de repouso em fertilizantes - (:unkn) unknown (Universidade Federal de Goiás, 2019)
This dissertation presents a statistical study and experimental study to analyze the rest angle measurement system in fertilizers of different particle sizes (1.5 mm <d50 <5 mm) and also analyzes the influence of particle size, height and side bars on the angle measurement. In the fertilizer industry, the angle of repose is an important design parameter for various equipment. This angle is also used to infer the degree of fluidity of the fertilizer. Due to its importance, there are different methods for determining this angle of repose in the literature, but the methods often have different and non-standard values. Therefore, the objective of this dissertation is to validate the measurement system based on the Repeatability and Reproductivity (R&R) study, of a technical apparatus built to measure the angle of repose of fertilizers. The apparatus was built based on the fixed funnel technique and the angle measurement was performed by analyzing photographic images using the “Image J” computer software. For the experiments were selected 3 (three) operators and separated 10 (ten) samples that contained different particle size. With the application of the study it was possible to identify that the proposed initial method presented a great variation, being classified as unacceptable. After investigating the causes of variation and change in the standard operating procedure, a new result was achieved and the measurement system index that previously had a high variation of 59.93% was reduced to 4.82%. And regarding the process factors investigated, using statistical techniques of multiple linear regression analysis, it was concluded that all of them (particle size, height and side bars) influence the rest angle value.
Analysis of the measurement system and rest angle factors in fertilizers
Keywords: Repetitividade; Reprodutividade; Ângulo de repouso e fertilizantes; Repeatability; Reproducibility; Rest angle and fertilizers; ENGENHARIAS::ENGENHARIA DE PRODUCAO